A Glass Beaker with Inscription from the Ancient City of Philadelpheia (Isauria – Cilicia Tracheia) - Hatice Körsulu (Gephyra)
The subject of this paper is a glass beaker with an inscription found in the necropolis of the Isaurian city of Philadelpheia. It bears the inscription "katakhaire kai euphrainou" in ancient Greek, a motto that can be translated as “Rejoice and be merry”. It was found, along with numerous other vessels, during a rescue excavation conducted in a refuse heap in the necropolis of the ancient city of Philadelpheia, situated north of the village of Gökçeseki in the Ermenek district of Karaman province. The glass beaker from Philadelpheia, of which other examples of its type are documented in the literature, appears to be the only example so far discovered in Anatolia. It is dated to between the 2nd half of the 1st century AD and the beginning of the 2nd century AD. The “motto” or “phrase” on the glass expresses good wishes. This must be intended for “wishing good health” to those who were served drinks in these vessels. The beaker was produced using the mould-blowing technique. It is decorated from below the rim to the lowermost part of its body with horizontal and vertical floral and geometric motifs in relief. The inscription is in the main frieze on the body. The glass was blown into a two-part mould. The similarities in decoration, height and width between this glass and the ones found in Syria indicate a Syrian origin for this glass, which is the most commonly suggested origin for this type of beaker.